Pengembangan Model Kewirausahaan Dalam Rangka Meningkatkan Kualitas Kurikulum Pendidikan Melalui Pemanfaatan Teknologi Kecerdasan Buatan - Suputra, I Gede Kahar; Sudewa, Jaka (Coopetition : Jurnal Ilmiah Manajemen, 2024)
This study explores the impact of integrating ChatGPT into the Project-Based Learning (PBL) model on students' entrepreneurial competencies at IKOPIN University. The background of this research is the need for innovative learning approaches in the era of the Fourth Industrial Revolution, focusing on the role of artificial intelligence in education. The study employs a quantitative approach with an explanatory survey design, collecting data from students participating in the KBBK program based on PBL integrated with ChatGPT. The sample was selected purposively, and the data were analyzed using Structural Equation Modeling (SEM). The Confirmatory Factor Analysis results indicate a good model fit after the removal of 16 indicators, leaving 8 indicators with a CMIN/DF of 1.406, a P-value of 0.122, a GFI of 0.973, and an RMSEA of 0.045. The results show that PBL has a significant positive impact on the use of ChatGPT (coefficient 0.068) and the enhancement of entrepreneurial competencies (coefficient 0.083). Instrument validity was tested with factor loadings above 0.5, and reliability was confirmed with Cronbach's Alpha above 0.7. This study emphasizes the importance of technology integration in education to enhance students' competencies, with recommendations for improving infrastructure, training, and developing an adaptive curriculum.